2021
DOI: 10.3390/v13081637
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Live-Attenuated Vaccines against Herpes Simplex Viruses

Abstract: Diseases caused by human herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) affect millions of people worldwide and range from fatal encephalitis in neonates and herpes keratitis to orofacial and genital herpes, among other manifestations. The viruses can be shed efficiently by asymptomatic carriers, causing increased rates of infection. Viral transmission occurs through direct contact of mucosal surfaces followed by initial replication of the incoming virus in skin tissues. Subsequently, the viruses infect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
(92 reference statements)
0
17
0
1
Order By: Relevance
“…The vaccine was previously tested without FDA approval in a small group of HSV-infected patients. The investigators reported a reduction in the recurrence rates in this group [ 198 , 199 ].…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine was previously tested without FDA approval in a small group of HSV-infected patients. The investigators reported a reduction in the recurrence rates in this group [ 198 , 199 ].…”
Section: Vaccinesmentioning
confidence: 99%
“…HSV vaccines currently under investigation are shown in Table 5 [ 158 , 190 , 194 , 195 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ].…”
Section: Vaccinesmentioning
confidence: 99%
“…In addition to antiviral research, there has been a decades-long effort to develop a HSV vaccine without success. However, there are numerous active clinical and preclinical studies for HSV vaccines, including several utilizing the promising new technology of messenger ribonucleic acid (RNA)-based vaccines, which has been highly successful against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 34 ].…”
Section: Herpes Simplex Virus 1 (Hsv1)mentioning
confidence: 99%
“…Primary infection with HSV-1 occurs by virus penetration at mucosal surfaces or through skin abrasions. From here, HSV-1 infects innervating sensory nerves of the trigeminal or dorsal root ganglia, where it establishes a life-long latent infection with a high rate of periodical reactivation [ 2 , 5 , 6 , 7 ]. The current predominant antiherpetic agents are viral deoxyribonucleic acid (DNA) extension inhibitors, such as acyclovir (ACV), penciclovir, valacyclovir, famciclovir, foscarnet, and cidofovir.…”
Section: Introductionmentioning
confidence: 99%